Mergers in imperfectly segmented markets - Pio Baake; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We present a model with firms selling (homogeneous) products in two imperfectly segmented markets (a high-demand and a low-demand market). Buyers are mobile but restricted by transportation costs, so that imperfect arbitrage occurs when prices differ in both markets. We show that equilibria are distorted away from Cournot outcomes to prevent consumer arbitrage. Furthermore, a merger can lead to an equilibrium in which only the high-demand market is served. This is more likely (i) the lower consumers' transportation costs and (ii) the higher the concentration of the industry. Therefore, merger incentives are much larger than standard analysis suggests.
Keywords: D43; L13; L41; 330; Imperfect market segmentation; oligopoly; price discrimination; consumer arbitrage; mergers; Übernahme; Fusion; Ökonomischer Anreiz; Oligopol; Unvollkommener Markt; Marktsegmentierung; Preisdifferenzierung; Wechselkosten; Transportkosten; Theorie